P 16. Multichannel anodal transcranial direct current stimulation over the right inferior frontal gyrus in pediatric population: preliminary behavioural results. Issue 8 (August 2021) - Merschformann, C.; Splittgerber, M.; Borzikowsky, C.; Papadimitriou, K.; Salvador, R.; Breitling-Ziegler, C.; Brauer, H.; Krauel, K.; Prehn-Kristensen, A.; Nees, F.; Dempfle, A.; Siniatchkin, M.; et al.
Abstract : Introduction. Non-invasive neuromodulation via transcranial direct current stimulation (tDCS) is a promising method for modulating plasticity. For the first time multichannel tDCS was used to investigate a larger number of children and young adolescents. Previous studies suggest that tDCS affects cognitive functions. It is assumed that the inferior frontal gyrus (IFG) has an important role in the process of response inhibition. Therefore, multichannel tDCS might has potential as therapy option for neurodevelopmental diseases such as attention deficit hyperactivity disorder (ADHD). The present study addressed the question whether tDCS could modulate this function. In addition, the study intended to investigate the most effective timing and tolerance of stimulation. Methods. The study was approved by the Ethic Committee of the Faculty of Medicine of Kiel university. 29 healthy participants (10-17 years old, mean age: 14, 2 years, SD 2, 14) were included in the analysis in a double-blinded and sham-controlled crossover study. The Flanker-task was used as target-task so that reaction time and accuracy were focused in the evaluation. Stimulation was scheduled prior (offline) or during (online) target task. After that the participants completed the n-back-task and the CPT-task as non-target-tasks. Resting state EEG was recorded before and after stimulation. Additionally, task related EEG was performed to expose changes at the neurophysiological level. For multichannel 2 mA tDCS over the right IFG we used a 6-channel solution (3.14 cm2 circular electrodes, positioned at F8 (1000 µA), FC6 (999 µA), P7 (−377 µA), T8 (−422 µA), C6 (−577 µA) and FPZ (−623 µA), filled with EEG electrode gel). Current was ramped up for 30 seconds at the beginning and the end in sham as well in verum stimulation. A linear mixed model was used for statistical evaluation. Results. There were only a few participants showing side effects such as itching, burning or fatigue. In a total of 112 sessions there were eight cases of adverse events such as headache. Our preliminary results at the behavioural level show no significant differences ( p > 0.05) between tDCS and sham stimulation. There were no significant effects on accuracy or reaction time between online or offline stimulation neither. Conclusion. Our results show that tDCS was tolerated well by the participants. Based on preliminary results we could not confirm that tDCS could modulate the rIFG because response inhibition was not affected significantly. Further analysis could find out about possible reasons for our results such as ceiling effects. Analysis of resting EEG prior and after stimulation as well as task related EEG might yield neurophysiological explanation for the absence of behavioural improvement outcomes. The results provide a basis for future studies such as investigations of ADHD patients and might offer a compatible therapy option.